Membangun Jiwa Entrepreneur Gen-Z melalui Pelatihan Tata Rias Berbasis BNSP - Hosnaini, Luluk; Sholikhah, Jenny Almas; Mufidah, Munfaridatul; Fitri, Nabilah; Ismaya, Miladia Izza; Wati, Qoyum Kurnia; Dewi, Nabilah Chintya; Rizfa Faiza, Nurlaili Adkhi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Unemployment in Kediri City, especially among women of productive age, is a challenge that requires solutions based on community empowerment. This BNSP-based makeup training program aims to improve work skills, instill an entrepreneurial spirit, and create independent business opportunities. The method used is through training. The implementation of the training includes intensive practice sessions, group discussions, and entrepreneurial mentoring. As a result, participants not only master makeup techniques, but also have a simple business plan to start an independent business. This training has succeeded in improving the work skills and economic independence of participants, while contributing to reducing unemployment in Kediri City. This program shows that community-based empowerment can be an effective solution to social challenges.